First demonstration of OH suppression in a high-efficiency near-infrared spectrograph. Issue 2 (8th January 2020) - Ellis, S C; Bland-Hawthorn, J; Lawrence, J S; Horton, A J; Content, R; Roth, M M; Pai, N; Zhelem, R; Case, S; Hernandez, E; Leon-Saval, S G; Haynes, R; et al.
ABSTRACT: Ground-based near-infrared (NIR) astronomy is severely hampered by the forest of atmospheric emission lines resulting from the rovibrational decay of OH molecules in the upper atmosphere. The extreme brightness of these lines, as well as their spatial and temporal variability, makes accurate sky subtraction difficult. Selectively filtering these lines with OH suppression instruments has been a long standing goal for NIR spectroscopy. We have shown previously the efficacy of fibre Bragg gratings (FBGs) combined with photonic lanterns for achieving OH suppression. Here we report on PRAXIS, a unique NIR spectrograph that is optimized for OH suppression with FBGs. We show for the first time that OH suppression (of any kind) is possible with high overall throughput (18 per cent end-to-end), and provide examples of the relative benefits of OH suppression.